The Socio-Economic Characteristics of Respondents Influence Their Perceptions of Tourism's Contributions To Sustainable Development Goals In Osun State Communities. - Ajani , Adenike Adeniyi; Adeleke , Bola Olusola; Ogunsusi , Kayode (Corpus Intellectual, 2025)
This study investigates how socioeconomic characteristics influence perceptions of tourism’s contributions to Sustainable Development Goals (SDGs) in Osun State communities. Recognising the pivotal role of tourism in sustainable development, this research focuses on the demographic factors shaping local perceptions. A quantitative approach was employed, utilising a structured questionnaire administered to a stratified sample of respondents. Data were analysed using descriptive statistics to reveal trends and correlations among socio-economic characteristics and perceptions of tourism. The findings indicate that younger individuals (18-35 years) constitute 65% of the sample, suggesting a tendency to prioritise job creation and economic opportunities linked to tourism, while older respondents (35%) may emphasise cultural preservation and environmental sustainability. Gender distribution shows 55% female respondents, potentially influencing perspectives on community involvement and social equity in tourism development. Income levels reveal that 46.67% are middle-income earners, likely fostering favourable perceptions of tourism’s economic benefits, whereas low-income individuals (30%) may focus on accessibility and equitable benefit-sharing. Educational attainment is high, with 46.67% holding tertiary degrees, indicating greater awareness of global issues like SDGs and advocacy for responsible tourism practices. The study concludes that socio-economic characteristics significantly shape perceptions of tourism’s contributions to SDGs in Osun State, highlighting the need for inclusive tourism strategies that consider diverse community perspectives.